Associativity as a strategy to manage business development processes and solution to social problems - Ospina Penagos, Albeiro
Constant change, economic instability, poor access to resources for some sectors, personal crises and uncertainties are characteristic features in today’s personal and business contexts. Networks, alliances, associations and groups; Are a mechanism of cooperation between companies and / or individuals, where their participation is voluntary and is used to obtain individual benefits (strengthening, sustainability, consumption, economies of scale, market access, innovation, and social problems) Articulated of the members. This study, applied, documental, descriptive, qualitative, and exploratory, is oriented to the analysis and description of some associative schemes as a strategy to manage the processes of business development and solution to social problems. The findings found, evidenced associativity strategies such as: networks, fairs, shared consumption, cluster, temporary or definitive alliances; One of the most important elements for its creation is the construction and maintenance of these associations are the bonds of trust between the members and the community over time. The benefits of forming partnerships for organizations allow: To add efforts, talents and wills, Maximizing efforts, minimizing costs, improving quality, providing sustainability, improving competitiveness in general and achieving greater social welfare.